'The Bond of Civility': Roger Williams on toleration and its limits - Bejan, T (Taylor and Francis, 2012)
In this article, I examine the meaning of the concept of ‘civility’ for Roger Williams and the role it played in his arguments for religious toleration. I place his concern with civility in the broader context of his life and works and show how it differed from the missionary and civilizing efforts of his fellow New English among the American Indians. For Williams, civility represented a standard of inclusion in the civil community that was ‘essentially distinct’ from Christianity, which properly governed membership in the spiritual community of the church. In contrast to recent scholarship that finds in Williams a robust vision of mutual respect and recognition between co-citizens, I argue that civility constituted rather a very low bar of respectful behavior towards others entirely compatible with a lack of respect, disapproval, and even disgust for them and their beliefs. I show further that civility for Williams was consistent with—and partially secured by—a continued commitment on the part of godly citizens to the potential conversion of their neighbors. Williams endorsed this ‘mere’ civility as a necessary and sufficient condition for toleration while also delineating a potentially expansive role for the magistrate in regulating incivility. Contemporary readers of William who conflate civility with other good things, such as mutual respect, recognition, and civic friendship, slide into a position much like that he was trying to refute.